Effects of Yulangsan polysaccharide on monoamine neurotransmitters, adenylate cyclase activity and brain-derived neurotrophic factor expression in a mouse model of depression induced by unpredictable chronic mild stress - Liang, Shuang; Huang, Renbin; Lin, Xing; Huang, Jianchun; Huang, Zhongshi; Liu, Huagang (Neural regeneration research, 2012)
The present study established a mouse model of depression induced by unpredictable chronic mild stress. The model mice were treated with Yulangsan polysaccharide （YLSPS; 150, 300 and 600 mg/kg） for 21 days, and compared with fluoxetine-treated and normal control groups. Enzyme-linked immunosorbent assay, radioimmunity and immunohistochemical staining showed that following treatment with YLSPS （300 and 600 mg/kg）, monoamine neurotransmitter levels, prefrontal cortex adenylate cyclase activity and hippocampal brain-derived neurotrophic factor expression were significantly elevated, and depression-like behaviors were improved. Open-field and novelty-suppressed feeding tests showed that mouse activity levels were increased and feeding latency was shortened following treatment. Our results indicate that YLSPS inhibits depression by upregulating monoamine neurotransmitters, prefrontal cortex adenylate cyclase activity and hippocampal brain-derived neurotrophic factor expression.